Subclinical Hyperthyroidism and the Cardiovascular Disease - Delitala, Alessandro P. (Hormone and metabolic research, 2017)
Abstract Thyroid hormone excess has complex metabolic effects, particularly on the cardiovascular system. Treatment of these conditions is universally suggested by international guidelines. Subclinical hyperthyroidism, defined by reduced or suppressed TSH levels in the presence of normal free thyroxine and free triiodothyronine values, is common in the general population and progressively increases with aging, being as high as 15.4% in subjects more than 75 years old and more frequent in subjects with nodular goiter. Subclinical hyperthyroidism is often asymptomatic and the diagnosis is incidentally made during screening exams. However, this form of thyroid disorder has gained attention in the last years for its association with cardiovascular disease, in particular with atrial fibrillation. Less clear are the effects of subclinical hyperthyroidism on blood pressure, stroke, or heart failure. The decision to treat subclinical hyperthyroidism is made on the clinical judge, particularly in elderly patients and/or in the presence of comorbidities.